2006
DOI: 10.1016/j.abb.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan a sulfated polysaccharide from brown algae is a potent modulator of connective tissue proteolysis

Abstract: Fucoidans are sulfated fucosylated polymers from brown algae cell wall that exhibit some heparin/heparan sulfate properties. We previously demonstrated that these polysaccharides were able in vitro to stimulate dermal fibroblast proliferation and extracellular matrix deposition. Here, we investigated the action of a 16kDa fucoidan fraction on parameters involved in connective tissue breakdown. This fucoidan is able to inhibit gelatinase A secretion and stromelysin 1 induction by interleukin-1beta on dermal fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(85 citation statements)
references
References 48 publications
3
82
0
Order By: Relevance
“…The intensity of biological activities of fucoidan varies with species, molecular weight, composition, structure and the route of extraction (Fitton 2011), and its non-animal origin brings particular pharmacological activities (Senni et al 2006). Fucoidan has been well studied for its antitumor (Hsu et al 2013), antiviral (Tengdelius et al 2014), anti-inflammatory (Hwang et al 2011), and anticoagulant (Irhimeh et al 2009) activities.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of biological activities of fucoidan varies with species, molecular weight, composition, structure and the route of extraction (Fitton 2011), and its non-animal origin brings particular pharmacological activities (Senni et al 2006). Fucoidan has been well studied for its antitumor (Hsu et al 2013), antiviral (Tengdelius et al 2014), anti-inflammatory (Hwang et al 2011), and anticoagulant (Irhimeh et al 2009) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidan is of particular pharmacological interest because its non-animal origin, exhibits anti-inflammatory activities and potent modulation of connective tissue proteolysis (Senni et al, 2006). Ina addition, their anticoagulant and antithrombotic, antitumor, antiviral, anti-complement and anti-inflammatory activities (Be´ress et al, 1993;Patankar et al, 1993;Blondin et al, 1996;Haroun-Bouhedja et al, 2000;Bojakowski et al, 2001;Marais and Joseleau, 2001) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fucoidans are sulfated fucosylated polymers that exhibit the properties of heparin/ heparan sulfate and the capacity to control parameters involved in connective tissue destruction in human skin. Studies have indicated that the SPs of the red microalga Porphyridium have antiviral and antioxidant activity, while those from Phaeodactylum and Chlorella have anti-infl ammatory activity [Raposo et al, 2013;Senni et al, 2006]. Sulfated polysaccharides, as well as cellulose and other beta glucans, can also be considered dietary fi ber, which is not digested, but rather fermented by intestinal bacteria to produce short-chain fatty acids; these have been recognized as mediators in intestinal immune function.…”
Section: Carbohydratesmentioning
confidence: 99%